2018
DOI: 10.5539/jas.v10n7p196
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical Parameters of Honey From Melipona mondury Smith, 1863 (Hymenoptera: Apidae: Meliponini)

Abstract: The physico-chemical properties of honey produced by the stingless bee Melipona mondury from Atlantic Forest in the state of Bahia, northeastern Brazil were evaluated. The evaluated characteristics included: water content, electrical conductivity, pH, acidity, water activity, ashes, diastase, hydroxymethylfurfural (HMF), reducing sugars and saccharose values. The honey samples showed mean values of 29.18% for moisture; 391.5 μS for electrical conductivity; pH of 4.06; 34.3 meq kg -1 for acidity; 0.73 for water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…From this it is demonstrated that stingless bee honey in general has higher moisture content than A. mellifera honey. This may be due to the high hygroscopicity nature of stingless bee (Meliponinae) honey ( Alves et al., 2005 ; do Nascimento et al., 2015 ) indicating that the moisture content in honey in turn can be influenced by intrinsic characteristic of bee species and the material they used to construct for their honey storage. For instance, stingless bees use unique cerumen made up of wax combined with propolis and plant resins to construct their honey pots for honey storage which may contribute to high moisture content as compared to honey combs of Apis spp .…”
Section: Resultsmentioning
confidence: 99%
“…From this it is demonstrated that stingless bee honey in general has higher moisture content than A. mellifera honey. This may be due to the high hygroscopicity nature of stingless bee (Meliponinae) honey ( Alves et al., 2005 ; do Nascimento et al., 2015 ) indicating that the moisture content in honey in turn can be influenced by intrinsic characteristic of bee species and the material they used to construct for their honey storage. For instance, stingless bees use unique cerumen made up of wax combined with propolis and plant resins to construct their honey pots for honey storage which may contribute to high moisture content as compared to honey combs of Apis spp .…”
Section: Resultsmentioning
confidence: 99%
“…Melipona mondury (Uruçú-Amarela) is one of Brazil's stingless bee species exploited for honey ( Pimentel et al, 2022 ). However, the intensive culture of this specie is incipient, and the physicochemical characteristics of the produced honey are scarcely reported ( Alves et al, 2018 ). Furthermore, as far as the authors know, only one study performed a metagenomic analysis on honey produced by the bee of this species ( Echeverrigaray et al, 2021 ), still, it evaluated only the biodiversity of yeasts.…”
Section: Introductionmentioning
confidence: 99%
“…M. quadrifasciata, grown throughout the Atlantic Forest, exhibits moisture values higher than twice the reference value (BILUCA et al, 2016 e refs.). In the case of Melipona mondury (urucu-amarela), only the activity of diastasis is within limits accepted by current legislation (ALVEZ et al, 2018).…”
Section: Stingless Productsmentioning
confidence: 99%